Using text-to-image generative AI to create storyboards: Insights from a college psychology classroom - Tilak, Shantanu; Bagley, Blake; Cantu, Jadalynn; Cosby, Mya; Engelbert, Grace; Hammonds, Ja'Kaysiah; Hickman, Gabrielle; Jackson, Aaron; Jones, Bryce; Kennedy, Kadie; Kennedy, Stephanie; King, Austin; et al. (Journal of Sociocybernetics, 2024)
This participatory study, conducted in an introductory psychology class, recounts self-reflections of 22 undergraduate students and their instructor engaging in a GenAI-mediated storyboard generation process. It relies on Gordon Pask’s conversation theory, structuring out the nature of interactions between students, instructor, and GenAI, and then uses a qualitative narrative to describe these conversational feedback loops constituting the creation of draft and final storyboards. Results suggest students engaged in cyclical feedback driven processes to master their creations, used elements of photography related to the relationships between objects in frame, image processing, and cultural objects/themes to generate narratives. Issues were faced with generating text on images, and the consistency and style of generated frames as they interacted with GenAI tools. This study provides guidelines to university teaching professionals to design effective activities mediated by text-to-image GenAI.